Comprehensive Insights into Medicinal Research on Imidazole-Based Supramolecular Complexes - Shu-Rui Li; Yi-Min Tan; Ling Zhang; Cheng-He Zhou (MDPI AG, 2023)
The electron-rich five-membered aromatic aza-heterocyclic imidazole, which contains two nitrogen atoms, is an important functional fragment widely present in a large number of biomolecules and medicinal drugs; its unique structure is beneficial to easily bind with various inorganic or organic ions and molecules through noncovalent interactions to form a variety of supramolecular complexes with broad medicinal potential, which is being paid an increasing amount of attention regarding more and more contributions to imidazole-based supramolecular complexes for possible medicinal application. This work gives systematical and comprehensive insights into medicinal research on imidazole-based supramolecular complexes, including anticancer, antibacterial, antifungal, antiparasitic, antidiabetic, antihypertensive, and anti-inflammatory aspects as well as ion receptors, imaging agents, and pathologic probes. The new trend of the foreseeable research in the near future toward imidazole-based supramolecular medicinal chemistry is also prospected. It is hoped that this work provides beneficial help for the rational design of imidazole-based drug molecules and supramolecular medicinal agents and more effective diagnostic agents and pathological probes.